Correction: Effect of graphene oxide on anticorrosion performance of polyelectrolyte multilayer for 2A12 aluminum alloy substrates. Issue 58 (25th July 2017) - Zhao, Xia; Jin, Zuquan; Zhang, Binbin; Zhai, Xiaofan; Liu, Shuan; Sun, Xiaolin; Zhu, Qingjun; Hou, Baorong
Abstract : Correction for 'Effect of graphene oxide on anticorrosion performance of polyelectrolyte multilayer for 2A12 aluminum alloy substrates' by Xia Zhao et al., RSC Adv., 2017, 7, 33764–33774.